(3GdeLdS GdOhdi dMbhb GdEfSGf (B/ s - (3CMeO YRJ OjGH GHQGgje s; (3CTQa YQaGJ SdjeGf GHh MLGRg s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3JgOa GdOQGSI dJMdjd eOi eG jeKd EfTGA GdeLdS GdOhdi dMbhb GdEfSGf ef MeGjI hJYRjR dEMJQGe hMeGjI Mbhb GdGfSGf (B:(3heOi GdJWhjQ ai efXheI GdCee GdeJMOI dMeGjI hJYRjR Mbhb GdEfSGf (B. (3hbO YQVJ GdOQGSI dfTCI GdeLdS GdOhdi dMbhb GdEfSGf (B:(3hGdPi Md eMd dLfI GdCee GdeJMOI dMbhb GdEfSGf (B:(3ai Xd eMGhdI dEUdGM efXheI GdCee GdeJMOI HUaI YGeI hMbhb GdEfSGf HUaI NGUI (B:(3hJfGhdJ GdOQGSI fXGe GdYVhjI HGdeLdS hcPdc fXGe GdJUhjJ hEJNGP GdbQGQGJ (B:(3HGdGVGaI Gdi eHGOF Yed GdeLdS hCgOGag hYdGbJg HGdCee GdeJMOI hCLgRJgG hSGFQ GdefXeGJ GdMchejI hZjQ GdMchejI hGdeDSSGJ GdhWfjI dMbhb GdEfSGf (B:(3hcPdc JfGhdJ GdOQGSI BdjGJ GdeLdS hCSGdjH Yedg (B:(3hGdOhQ GdPi jbhe Hg ef CLd JYRjR EMJQGe hMeGjI Mbhb GdEfSGf (B:(3heOi fLGM GdeLdS ai JMbjb Pdc s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi , (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B334-367s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3GdbGfhf GdOhdi dMbhb GdGfSGf s; (3GdeLdS GdOhdi dMbhb GdEfSGf s; (3dLfI GdGee GdeJMOI dMbhb GdEfSGf s; (3Jbjje GdeLdS GdOhdj dMbhb GdGfSGfs; (3GdeDSSGJ GdhWfjI dMbhb GdGfSGfs; (3GdjGJ MeGjI Mbhb GdGfSGfs; (3GdefXeGJ ZjQ GdMchejIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs